Berkshire encyclopedia of human-computer interaction - Bainbridge, William Sims (Gale virtual reference library., 2004)
Examines how people interact and communicate via computers, robots, information systems, and the Internet. Articles present current research in sociology, behavioral science, anthropology, engineering, computer science. Written for the educated layperson.